Assessment of Distress Among Chemotherapy Patients: A Comparative Study of Gender - Bergerot, Cristiane Decat; Araujo, Tereza Cristina Cavalcanti Ferreira de; Tróccoli, Bartholomeu Tôrres (Paidéia (Ribeirão Preto), 2014)
The aim of this study was to evaluate, analyze and understand distress levels experienced during chemotherapy treatment, comparing men and women. The sample was composed of 328 patients recruited from an Oncology center. Data collection included the application of the Distress Thermometer at three stages of chemotherapy: beginning, middle and end. Incidence of distress decreased in both genders over the course of assessments. Comparatively, the incidence was higher among women, who also reported the highest number of problems in the practical, family, emotional, spiritual and physical domains. The results corroborate the international literature on the subject. Clinical interest of systematic assessment of distress was confirmed to develop routines of therapeutic monitoring adapted to the specific needs of cancer patients.